Proceedings of the International Workshop on the Polychaetes of the Andaman Sea - Phuket Marine Biological Center, Department of Fisheries, Thailand, 3 June -27 August 1997. - Jacobsen, D.E. (ed.). (Thailand Phuket Marine Biological Center, 1997)
Phuket Marine Biological Center Special Publication no. 24
Keywords: Polychaeta--Andaman Sea--Congresses.; Polychaeta--Thailand--Congresses.